Lateralization and Decreased Neck-Shaft Angle Reduces Scapular Notching and Heterotopic Ossification. Issue 23 (1st December 2020) - Zitkovsky, Helen S.; Carducci, Michael P.; Mahendraraj, Kuhan A.; Grubhofer, Florian; Jawa, Andrew
Abstract : Background: Lateralization of the glenosphere in reverse shoulder arthroplasty likely mitigates scapular notching; however, there is a paucity of data evaluating the effect of heterotopic ossification (HO) at the inferior aspect of the glenoid neck. Methods: We retrospectively reviewed 107 consecutive reverse shoulder arthroplasty patients between April 2013 and April 2016. During the study period, the surgeon switched from a 2.5-mm lateral center of rotation and a 155° neck-shaft angle (NSA) to a 6- or 10-mm lateralized design with a 135° NSA. Preoperative and minimum 2-year postoperative patient-reported outcomes and range of motion were collected. Two-year postoperative radiographs were evaluated for scapular notching and HO. Results: The lateralized center of rotation implant was 72% less likely to develop HO and 85% less likely to produce scapular notching than the medialized prosthesis. Conclusion: Implants with laterally offset glenospheres and 135° NSA may decrease postoperative HO and scapular notching. Level of Evidence: Level III, retrospective cohort study.